PREDICTION OF STRAWBERRY CHEMICAL COMPOSITION BY IMAGING ANALYSIS PROCESSES - Tarek FOUDA; Adel ELMETWALLI; Shimaa SALAH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The goal of this research is to analyze images of strawberry fruits and related the results with chemical properties under using different applications of gibberellic acid and citrate potassium. The work was carried on spring 2016 at private farm in Tanta ELgharbia governorate, Egypt. The chemical properties such as the total soluble solid and anthocyanin was determined under different treatments and related with images indices. The ENVI software package was used to analyze the images of orange fruits and three bands, RGB, (red, green, blue) were derived for each image until obtaining the R, G, B colors then color indices Red/ Green ratio (R/G), hue, intensity (I). The results showed that there are significant correlation with some chemical and color indicators. The results obtained in this research demonstrated that hue, intensity and R/G ratio indices gives understanding about and total soluble solid and anthocyanin.